Brown-shell eggs shows high incidence of blood and meat spots accompanied by unique microbial distribution patterns - Wu, Junfeng; Yan, Yiyuan; Chen, Jiahua; Li, Junying; Li, Guangqi; Wu, Guiqin; Wang, Bin; Zheng, Gang; Yang, Yuqin; Du, Yushuang; Lian, Ling (Frontiers in Nutrition, 2025)
IntroductionThe blood and meat spots in eggs are recognized as defects for egg quality. The frequency of blood and meat spots in brown-shell eggs is much higher than that in white-shell eggs in previous studies. However, the actual occurrence frequency and their effects on the microbial composition in eggs remain poorly understood.MethodsIn this study, we examined the frequency of blood and meat spots in brown-shell and white-shell eggs, respectively, from Rhode Island Red and White Leghorn chickens at seven ages.ResultsThe results showed that blood and meat spots in brown-shell eggs exhibit much higher average frequency (63.99%) than that in white-shell eggs (1.37%). Furthermore, we analyzed the relationship between the presence of blood and meat spots and the microbial community distribution in the egg albumen and yolk. Briefly, we selected brown-shell eggs (n = 112) from Rhode Island Red, among which 51 eggs showing blood/meat spots were classified as RIR_CASE, and 61 normal eggs without blood/meat spot were classified as RIR_CON. Additional white-eggshell eggs (n = 124) without blood/meat spots from White Leghorn were selected as WL_CON. 16S rRNA sequencing was performed in both egg white and yolk. The results indicated that neither egg white nor yolk is sterile, with Proteobacteria identified as the dominant bacterial phyla. The microbial alpha diversity in both egg white and yolk of RIR_CASE was significantly lower compared to RIR_CON and WL_CON. Beta diversity analysis showed that the Weighted UniFrac Distance between RIR_CASE and RIR_CON in the egg yolk group was significantly larger than the distance between WL_CON and RIR_CON. It suggested that the difference of microbial diversity was mainly caused by blood and meat spots other than by chicken breeds. LEfSe analysis identified eight microbial taxa closely linked to the presence of blood and meat spots in egg white or yolk. Moreover, through the combination of random forest analysis, we identified the unique microbial biomarkers Comamonas_F and Chryseobacterium in the egg white of the RIR_CASE group.DiscussionOur study indicates that eggs with blood and meat spots occur at a higher frequency in brown-shell chickens and are accompanied by a distinct microbial community distribution.